2016
DOI: 10.4103/2008-7802.173792
|View full text |Cite
|
Sign up to set email alerts
|

Dairy consumption and risk of stroke: A case-control study

Abstract: Background:It remains controversial if dairy product intake is associated with risk of stroke. Limited information is available from Middle East countries in this regard. This case-control study was conducted to assess the relationship between dairy consumption and risk of stroke in Iranian adults.Methods:In this study, 195 stroke patients (recognized based on clinical findings and computed tomography scan) hospitalized in neurology ward of Alzahra University Hospital were enrolled. Controls (n = 195) were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In addition, an animal experiment confirmed that prolonged consumption of a high-fat diet aggravates the condition of stroke ( 20 ). An Iranian case-control study demonstrated that the risk of stroke increased as high-fat diet consumption increased ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an animal experiment confirmed that prolonged consumption of a high-fat diet aggravates the condition of stroke ( 20 ). An Iranian case-control study demonstrated that the risk of stroke increased as high-fat diet consumption increased ( 21 ).…”
Section: Discussionmentioning
confidence: 99%